2005
DOI: 10.1080/16501970510032622
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intensive training for children with cerebral palsy – a comparison between child and youth rehabilitation and conductive education

Abstract: No major differences were shown between the 2 training programmes. One intensive training period facilitated small improvements in gross motor function. The majority of children had a high consumption of training during the 1-year follow-up and the added value of repeated intensive training periods was limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…If needed, further probing was performed to elucidate parents' thoughts or perception of the group setting, the environment, intensity and parent-participation as these were considered to be characterizing aspects IGT. Since previous studies had shown similar outcome on functioning and parents' perception of the service-quality between two IGT in these settings [14,22,23], no difference was made whether training was performed within a child and youth habilitation approach or with the conductive education (CE) approach. The sequence of asking questions varied and parents'…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If needed, further probing was performed to elucidate parents' thoughts or perception of the group setting, the environment, intensity and parent-participation as these were considered to be characterizing aspects IGT. Since previous studies had shown similar outcome on functioning and parents' perception of the service-quality between two IGT in these settings [14,22,23], no difference was made whether training was performed within a child and youth habilitation approach or with the conductive education (CE) approach. The sequence of asking questions varied and parents'…”
mentioning
confidence: 99%
“…Rephrasing and probing were used to get a deeper understanding [24] (p.162). The interviewer was not involved in delivering any of the IGT but had experience working with disabled children and evaluating intensive training for children with CP [14,22,23]. …”
mentioning
confidence: 99%
“…However, there was no difference between the two training programmes in parents' perceptions of functional improvements after the ITP, which is in line with previously reported findings on functional outcomes. 19,20 Parent participation was less important if parents had previous experiences of training programmes. This implies that not all parents perceived that active parent participation was important for the child or themselves, in line with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Parents' perceptions of the service quality were investigated for the same cohort in a structured telephone interview after the ITP.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation